2010
DOI: 10.1007/s00432-010-0865-0
|View full text |Cite
|
Sign up to set email alerts
|

Second primary esophageal or lung cancer in patients with head and neck carcinoma in Taiwan: incidence and risk in relation to primary index tumor site

Abstract: The present dataset provides definite evidence that there is a substantial excess risk of second primary esophageal or lung cancer for the index tumors of oral cavity, pharynx and larynx. The absence of risk excess found in nasopharyngeal carcinoma is also compatible with the existing knowledge that it might have an entirely distinctive etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
0
40
0
1
Order By: Relevance
“…The development of second primary malignancy of esophagus, H&N region or lung in UADT cancer patients is high [4,5,7,22,23]. A nationwide study in Taiwan, where the prevalence of drinking alcohol, cigarette smoking and betel quid chewing is high, has shown that the standardized incidence ratio (SIR) of esophageal cancer in patients with head and neck cancer is significantly increased [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of second primary malignancy of esophagus, H&N region or lung in UADT cancer patients is high [4,5,7,22,23]. A nationwide study in Taiwan, where the prevalence of drinking alcohol, cigarette smoking and betel quid chewing is high, has shown that the standardized incidence ratio (SIR) of esophageal cancer in patients with head and neck cancer is significantly increased [4].…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide study in Taiwan, where the prevalence of drinking alcohol, cigarette smoking and betel quid chewing is high, has shown that the standardized incidence ratio (SIR) of esophageal cancer in patients with head and neck cancer is significantly increased [4]. Supported by the concept of “field carcinogenesis” [2], cancer may develop synchronously or metachronously in the UADT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major causes of death was the high incidence of second primary malignancies that jeopardized survival rates most in patients with early-stage disease. Previous studies indicated that patients with head and neck carcinoma had an increased risk of developing second primary malignancies, for which the head and neck regions, the esophagus and the lungs are the most usual sites (12,13). Survival after developing second primary cancers was poor, esophagus and lung being the worst (14 -16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, it remains unclear whether there are ethnic and geographic disparities in the incidence and patterns of second primary malignancies following the oral cavity cancers. In the present study, we have analyzed the incidence and risk of second primary cancers using a population-based cohort of 26 166 patients with an initial diagnosis of oral cavity cancers in Taiwan, a prevalent area of betel-nut chewing with over 40% of head and neck cancers occurring in the oral cavity (13).…”
Section: Introductionmentioning
confidence: 99%